Clinicopathological characteristics and treatment outcome of resectable gastric cancer patients with small para-aortic lymph node - Yao, Zhendan; Yang, Hong; Cui, Ming; Xing, Jiadi; Zhang, Chenghai; Zhang, Nan; Chen, Lei; Tan, Fei; Xu, Kai; Liu, Maoxing; Su, Xiangqian (Frontiers in Oncology, 2023)
Background: Resectable gastric cancer (GC) patients with small para-aortic lymph node (smaller than 10mm in diameter, sPAN) were seldom reported, and existing guidelines did not provide definite treatment recommendation for them. Methods: A total of 667 consecutive resectable GC patients were enrolled. 98 patients were in the sPAN group, and 569 patients without enlarged para-aortic lymph node were in the nPAN group. Standard D2 lymphadenectomy was performed. Neoadjuvant and adjuvant chemotherapy were administrated according to the cTNM and pTNM stage, respectively. Clinicopathological features and prognosis were compared between these two groups. Results: The median size of sPAN was 6 (range, 2−9) mm and the distribution was prevalent in No. 16b1. cN stage (p=0.001) was significantly related to the presence of sPAN. sPAN was both independent risk factor for OS (p=0.031) and RFS (p=0.046) of all patients. The prognosis of patients with sPAN was significantly worse than that of patients with nPAN (OS: p=0.008; RFS: p=0.007). Preoperative CEA and CA19-9 were independent risk factors for prognosis of patients with sPAN. Furthermore, patients in the sPAN group with normal CEA and CA19-9 exhibited acceptable prognosis (5-year OS: 67%; RFS: 64%), while those with elevated CEA or CA19-9 suffered significantly poorer prognosis (5-year OS: 17%; RFS: 17%) than patients in the nPAN group (5-year OS: 64%; RFS 62%) (both p < 0.05). Conclusions: Standard D2 lymphadenectomy should be considered a valid approach for GC patients with sPAN associate to normal preoperative CEA and CA19-9 levels. Patients with sPAN associated to elevated CEA or CA19-9 levels could benefit from a multimodal approach: neoadjuvant chemotherapy; radical surgery with D2 plus lymph nodal dissection extended to No. 16 station.